2021
DOI: 10.20473/jcmphr.v2i2.26821
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ramadan Fasting to Blood Pressure in Hypertensive Patients: A Meta-Analysis

Abstract: Ramadan fasting is a type of time-restricted eating and drinking. Previously, a systematic review drew inconclusive effect of Ramadan fasting on blood pressure in hypertensive individuals. Therefore, this meta-analysis aims to evaluate Ramadan fasting effects on blood pressure in hypertensive individuals. This literature search was conducted in PubMed and Google Scholar. All studies assessing the effect of Ramadan fasting on blood pressure in hypertensive patients were included. Statistical analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Other studies have reported improved BP control due to RF [ 70 – 72 ]. Two systematic reviews concluded the same [ 73 , 74 ]. Another meta-analysis suggested beneficial effects of RF on BP independent of changes in weight, total body water, and fat mass, supporting recommendations for some governmental guidelines that describe RF as a safe religious practice with respect to BP [ 75 ].…”
Section: Introductionmentioning
confidence: 86%
“…Other studies have reported improved BP control due to RF [ 70 – 72 ]. Two systematic reviews concluded the same [ 73 , 74 ]. Another meta-analysis suggested beneficial effects of RF on BP independent of changes in weight, total body water, and fat mass, supporting recommendations for some governmental guidelines that describe RF as a safe religious practice with respect to BP [ 75 ].…”
Section: Introductionmentioning
confidence: 86%